2014
DOI: 10.1684/ejd.2014.2282
|View full text |Cite
|
Sign up to set email alerts
|

Perceived impact of psoriasis on leisure-time activities

Abstract: Background: Psoriasis has an influence on various aspects of patients' everyday life. When estimating the total burden of the disease, the influence on leisure-time should also be taken into account. Objectives: To evaluate the perceived impact of psoriasis on leisure-time activities. Material and methods: The questionnaire study was based on 262 patients with psoriasis. The patients were asked to list their leisure-time activities, any activities they had reduced or given up completely because of psoriasis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
3
17
1
1
Order By: Relevance
“…This is different from the findings of a previous study among patients with psoriasis that used the same method of soliciting the list of affected activities [29]. This difference might be due to different manifestations of the diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…This is different from the findings of a previous study among patients with psoriasis that used the same method of soliciting the list of affected activities [29]. This difference might be due to different manifestations of the diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study [ 26 ] reported that sporting activities were significantly ( P < .001) affected among patients with mild, moderate, and severe psoriasis. Additionally, in a study by Leino et al, [ 28 ] 23.7% of patients had reduced their sporting activities while 30.2% had stopped completely. In accordance with these results, our meta-analysis exposes the relationship between the degree of exercise and prevalence of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Women comprised 45% of both the original sample and the respondents. Details about the patient sample, diagnosis, age and gender distributions have been reported previously [10]. …”
Section: Methodsmentioning
confidence: 99%